SELF-ASSESSMENT OF TEACHERS’ READINESS FOR IMPROVING THE TEACHING OF PSYCHOLOGICAL AND PEDAGOGICAL DISCIPLINES: THE RELEVANCE OF RESEARCH FOR UKRAINE - Larysa Petrenko (Alfred Nobel University Journal of Pedagogy and Psychology, 2025)
The article highlights the issue of improving the teaching of psychological and pedagogical disci- plines in higher education institutions in Ukraine in the context of integration into the European education- al space, digitalization, and social transformations. The purpose of the article is to define the morphology of teachers’ readiness for enhancing the teach- ing of psychological and pedagogical disciplines in higher education institutions and to analyse the results of self-assessment of the development level of this readiness. This allows for identifying the real profession- al development needs of teaching staff within departments. To achieve this aim, the author used the following research methods: meta-analysis of dissertations and scientific publications to determine the essence of the concept of “teachers’ readiness for improving the teaching of psychological and pedagogical disciplines”, its structure and component content; self-assess- ment of the formation levels of the components of the phenomenon; online surveying with the use of Goog- with the use of Goog- Goog- le Forms to collect data and analyse the results; data processing and graphical presentation by means of Microsoft Excel and the Datawrapper digital tool. The increased focus on this topic is justified by the author through the need to provide psychological support and resilience for participants in the educational process, ensure the effective adaptation of the education system to extreme conditions, and prepare society for recovery and development during the post-war period. Enhancing the quality of teaching psychological and pedagogical disciplines is viewed as a condition for maximizing the effectiveness of educational services across all segments of the population throughout life, which contributes to the sustainable development of local communities and increases the social significance of professional education. Based on a meta-analysis of domestic and international research, the concept of “teachers’ readiness for improving the teaching of psychological and pedagogical disciplines” is defined as a multidimensional phenomenon encompassing professional motivation, self-analysis ability, openness to innovation, and proficiency in modern methods, technologies, tools, and self-education skills. The structure of this readiness is outlined, including motivational, cognitive, practical, reflective, emotional-value, organizational, communicative, and digital components, along with their descriptions. The survey results demonstrate that a significant proportion of teachers possess the necessary knowledge and practical skills to improve teaching. However, nearly half of the respondents showed only a moderate level of readiness, indicating the need for further development of both the theoretical and practical aspects of teachers’ professional competence. Conclusions. The results of assessing the degree of readiness of teachers for improving the teaching of psychological and pedagogical disciplines have clarified the relevance of the issue of prioritizing the digital training for organizing blended and online learning. Such a direction of training should include not only mastering the technical characteristics of digital tools and technologies and developing practical skills in their use, but also deepening the pedagogical and psychological aspects of digital interaction of subjects of the educational process for the development and implementation of effective original teaching methods and strategies. The data obtained serve as the basis for the development of targeted advanced training programs aimed at further developing all the components of teachers’ professional readiness for modern challenges in the field of psychological and pedagogical education, and providing them with scientific and methodological support.